Von Willebrand Factor, osteoprotegerin and protein C pathway in the pathogenesis of experimental cerebal malaria - O'Regan, Niamh (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2015)
Plasmodium falciparum malaria infection is associated with an early marked increase in plasma VWF levels, together with a pathological accumulation of hyperreactive ultra-large VWF (ULVWF) multimers. Given the established critical role of platelets in malaria pathogenesis, these increases in plasma VWF raise the intriguing possibility that VWF may play a direct role in modulating malaria pathogenesis.
Keywords: Molecular Medicine, Ph.D.; Ph.D. Trinity College Dublin.